The utility of decompressive craniectomy in severe traumatic brain injury in Saudi Arabia trauma centers. (7th June 2021) - Al-Jehani, Hosam; Al-Sharydah, Abdulaziz; Alabbas, Faisal; Ajlan, Abdulrazag; Issawi, Wisam Al; Baeesa, Saleh
ABSTRACT: Background : Decompressive craniectomy (DC) represents an effective method for intracranial pressure (ICP) reduction in cases of severe traumatic brain injury (TBI). However, little is known regarding the attitude of practicing neurosurgeons toward decompressive craniectomy (DC) in Saudi Arabia. Objective : We aimed to explore the perspective on DC among neurosurgeons in Saudi Arabia. Methods : An electronic survey was distributed via e-mail to members of the Saudi Association of Neurological Surgery (SANS). Results : A total of 52 neurosurgeons participated in this survey. The majority of these neurosurgeons practice in a governmental (95.2%), tertiary hospital (75.5%) with academic affiliations (77.6%). Most surgeons (71.4%) agreed that the DC approach for managing refractory ICP is supported by evidence-based medicine. The majority of the participants choose to perform DC on a unilateral basis (80%). Interestingly, DC followed by duraplasty was performed by only 71% of these surgeons, with 29% of the respondents not performing expansive duraplasty. Conclusion : In Saudi Arabia, the utility of DC in cases of TBI with refractory intracranial hypertension has not been clearly defined among practicing neurosurgeons. The development of appropriate, widely adopted TBI guidelines should thus be a priority in Saudi Arabia to reduce variability among TBI care practices. In addition, a national TBI registry should be established for documenting different practices and longitudinal outcomes.